Ultrafine FeCu Alloy Nanoparticles Magnetically Immobilized in Amine‐Rich Silica Spheres for Dehalogenation‐Proof Hydrogenation of Nitroarenes. Issue 54 (3rd September 2018) - Bao, Hongjie; Li, Yunong; Liu, Lei; Ai, Yongjian; Zhou, Junjie; Qi, Li; Jiang, Ruihang; Hu, Zenan; Wang, Jingting; Sun, Hongbin; Liang, Qionglin
Abstract: A novel core–shell structured nanocatalyst (Fe3 O4 @SiO2 ‐NH2 ‐FeCu nanoparticles) with ultrafine FeCu alloy NPs magnetically immobilized in porous silica has been fabricated. The obtained catalyst revealed excellent activity and chemoselectivity for catalyzing the hydrogenation of nitroarenes to corresponding anilines using hydrazine hydrate as the hydrogen source, and the reaction could be carried out smoothly in water, which is an environmentally friendly solvent. The FeCu alloy effectively prevented the dehalogenation of halonitroarenes, and X‐ray photoelectron spectroscopy (XPS) study showed that it resulted from the electron‐enrichment of Fe from Cu. A kinetics study indicated that the reaction order was about 1.5 towards 4‐CNB and the apparent active energy ( E a ) was 48.1 kJ mol −1, which is a relatively low value. Furthermore, the FeCu NPs are magnetically immobilized in the silica spheres (Fe3 O4 @SiO2 ), therefore the catalyst can be easily recovered by use of an external magnet and also possesses a long life time. Abstract : Hydrogenation but no dehalogenation : A dehalogenation‐proof hydrogenation catalyst has been fabricated with an FeCu alloy. The ultrafine FeCu NPs are confined in micro tunnel of silica shell and the electronic modification from Cu to Fe enhances the activity and selectivity. The FeCu NPs are magnetically immobilized to prolong the life time of the catalyst.